Pemeriksaan kesehatan kucing di Yogyakarta: Health Examination of Cat in Yogyakarta - Soedarmanto Indarjulianto; Hastari Wuryastuty; Slamet Raharjo; Hary Purnamaningsih; Guntari Titik Mulyani; Ida Tjahajati (Fakultas Peternakan Universitas Papua, 2023)
Cats are pets that many people, including in Yogyakarta, are keeping. Various kinds of diseases can attack cats, but not all owners are able to check their cat's health status. This community service aims to carry out health checks for cats owned by the community especially animal owners who are customers of the Veterinary Clinic of Internal Medicine, FVM-UGM. The service was carried out from April to October 2022 by checking the cat's health status directly. The service has been conducted and can carry out examinations and therapy of 20 cats. Based on the examination, it was found that 17 cats (85%) were diagnosed as sick and three healthy cats (15%). The three main diseases found were skin, digestive and urinary systems. Through medical examinations by students accompanied by veterinarians in the Department of Internal Medicine, cat owners have been invited to watch and given information regarding disease diagnosis, therapy, and how to administer medicine. The owner already understands the cat’s health status, agree to the action and treatment and can provide medicine for the sick cat. It was concluded that the community service for cat health examination had been successfully carried out on 20 cats, and the owner knew the condition of the cat and was able to give the medicine given. Key words: Cat Examination; Community Service; Veterinary Clinic